Cancer Neurology in Clinical Practice Neurological Complications of Cancer and its Treatment (Springer International Publishing, 2018)
This updated edition provides clinicians from various backgrounds and levels of training the information needed to optimally diagnose and manage neurologic complications of the nervous system. Organized into seven sections, this comprehensive volume begins with an overview of diagnostic studies for neurologic complications involving the nervous system. That is followed by sections on metastatic and non-metastatic complications of cancer involving the nervous system, and the interpretation, diagnosis, and management of common neuro-oncologic symptoms. The next section reviews the neurologic complications of cancer therapy, including corticosteroids, radiation therapy, chemotherapy, targeted molecular therapies, immunotherapies, hematopoietic stem cell transplantation, and infections involving the nervous system. The final section focuses on the most important neurologic complications in cancers arising from specific organs. In addition to capturing the latest advancements in the rapidly evolving fields of oncology and cancer neurology, the goal of this resource is to lead clinicians toward prompt diagnosis and intervention in order to improve patient quality of life. "This textbook is a valuable resource for medical oncologists and radiation oncologists, as well as neurologists and neuro-oncologists dealing with these patients. ... Overall, the chapters are well organized, clearly written, fairly balanced, and reasonably up to date. ... I would recommend it as a learning tool to physicians in training (medical students, residents, and fellows) and for more experienced physicians as both a review/ update and a way to gain more in-depth knowledge and insight into the neurologic problems of cancer patients." (John C. Flickinger, International Journal of Radiation Oncology Biology Physics, Vol. 73 (2), 2009) "The general organization of the book is logical and facilitates its practical and everyday use. ... Overall this textbook is very comprehensive and encompasses main neuro-oncological challenges. ... Schiff, Kesari and Wen have edited a very elegant and highly practical textbook, written by recognized authorities in their respective fields, which will be used by a wide range of medical and surgical specialists who are confronted on a daily basis with neurological manifestations of cancer in their practice." (I. Radovanovic and G. Zadeh, British Journal of Cancer, Vol. 100 (6), 2009).